THE INTERNET AS A LEARNING RESOURCE IN IMPROVING HIGH SCHOOL LEVEL STUDENTS' LEARNING MOTIVATIO - Meilan Matiti; Imam Mashudi (Jurnal Ilmu Pendidikan dan Budaya, 2024)
This article discusses the internet as a learning resource at the high school level, where high school is a level of education that covers various subjects and a higher level of complexity. At the high school level, the learning process involves deeper understanding, application of more complex concepts, and development of analytical and critical skills. Therefore, selecting the right learning resources is very important to help students achieve this goal. Based on experience, there are several types of learning resources that are commonly used at the high school level, such as textbooks, audio-visual media, and digital technology. Utilizing the internet as a learning resource conditions students to learn independently. In this digital era, access to information and learning is no longer limited by time and space. The Internet expands the scope of education, bringing new possibilities to improve the quality of learning. The use of the internet in schools and in teaching methods is essential to motivate students, helping them develop skills relevant to future demands. This article Qualitative research methods were chosen because they provide a suitable framework for exploring subjective understanding and interpretation from students' perspectives. From the discussion above, it can be concluded that the choice of learning resources in learning, especially at the high school level, has a great influence on student motivation and learning outcomes. Especially the use of the internet as a learning resource changes the dynamics of student learning, encouraging them to learn independently. Access that is not limited by space and time provides new opportunities to improve the quality of learning. Therefore, the role of the internet in schools and in teaching methods is essential to motivate students and help them develop skills relevant to future demands.